Proposed Strategies to Increase Conversion Rate and to Compete with the Competitor for Sarinah Speciality Store - Muhammad Alifiando Addikara (Borong Newinera Publisher, 2024)
This study examines the conversion rate performance of Sarinah Specialty Store and its rivalry with competitors, despite the store's significant role in promoting local Indonesian items and small and medium-sized enterprises (SMEs). This study aims to analyze the factors of the Indonesian society fondness and the consumer insights to enhance the conversion rate of purchases at the Sarinah Specialty Store. Additionally, it intends to develop a competitive strategy for batik and fashion products in the market. This study encompasses exploratory research, where data was collected from a of 120 participants and a survey website. The collected primary and secondary data was then put through qualitative approach to uncover the factors that trigger visits to the store and the specific preferences of batik and fashion consumers. The findings of this study offer a comprehensive understanding of how trigger factors can be utilized as attributes to formulate effective tactics, increase conversion rates, gain a competitive edge over rivals.